Evaluation of ULISYS Acceptance in UNTAG Surabaya Library - Imas Rahmadhtul Hidayah; Yanuastrid Shintawati; Dian Kristyanto (Record and Library Journal, 2022)
Background of the study: The functionality of the library information system needs to be improved for users be able to receive the system. Evaluation of user acceptance is one of the benchmarks for the successful implementation of library information systems. Purpose: This study aims to describe the response of acceptance from users to the UNTAG Library Information System (ULISYS). Method: This research used qualitative methods using interviews with 6 main informants according to criteria, observations at the UNTAG Surabaya Library, and documentation. Data validity and accuracy tests using source triangulation techniques. Data analysis techniques use the Miles and Huberman concept. Findings: The use of ULISYS which is considered easy is proven to be able to increase labor productivity from the Education Staff of UNTAG Surabaya Library. The positive attitude of users to use ULISYS is said to be the acceptance phase towards ULISYS. The desire of the Education Staff of UNTAG Surabaya Library to keep using existing information systems can affect the intensity of ULISYS use. Conclusion: ULISYS can be accepted by the Education Staff of UNTAG Surabaya Library with 4 factors that support the acceptance including ease of use factors, usefulness factors, attitudes towards using of information systems, and behavioral intention to use information systems.